SEJARAH DAN PERAN MUHAMMADIYAH DI DALAM PENDIDIKAN - Tridayatna AS, Weli; Mudafri, Fathiyyah Shabrina; Khairi, Indah Salma (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study is to explain the history of the Muhammadiyah Association and its role in the field of education. This research is a kind of qualitative research. Library studies are data analysis techniques. Research data is derived from readings related to research topics. The research was carried out by collecting a variety of literature such as journals, books, newspapers, magazines, and articles from the Internet that are relevant to the research topic. Subsequently, the sources were studied and thoroughly examined before reaching conclusions. Studies show that Muhammadiyah has helped a lot in education in the homeland. This is evident from the role of Muhammadiyah in the field of education from before independence to the present day. This is evident from the numerous educational institutions established by Muhammadiyah, ranging from elementary school to secondary level.